2019
DOI: 10.1038/s41598-019-41823-9
|View full text |Cite
|
Sign up to set email alerts
|

Direct differentiation of bone marrow mononucleated cells into insulin producing cells using pancreatic β-cell-derived components

Abstract: Transplantation of stem cell-derived insulin producing cells (IPCs) has been proposed as an alternative to islet transplantation for the treatment of diabetes mellitus. However, current IPC differentiation protocols are focused on generating functional cells from the pluripotent stem cells and tend to rely on multistep, long-term exposure to various exogenous factors. In this study, we addressed the observation that under stress, pancreatic β-cells release essential components that direct the differentiation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Following OCP treatment, we also noted increased expression of several interesting inflammation pathway members. Transforming growth factor-beta 1 (TGFB1) is an antiinflammatory cytokine that has been shown to play a role in endometriosis pathogenesis [47,48] and suppresses or promote endometrial cancer depending on CD73 expression [49]. Its decreased expression after OCPs will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Following OCP treatment, we also noted increased expression of several interesting inflammation pathway members. Transforming growth factor-beta 1 (TGFB1) is an antiinflammatory cytokine that has been shown to play a role in endometriosis pathogenesis [47,48] and suppresses or promote endometrial cancer depending on CD73 expression [49]. Its decreased expression after OCPs will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ribeiro et al found that human pancreatic islet-derived EVs improve the differentiation of iPSC cluster culture in 3-D collagen hydrogel with increased pancreatic marker expression (148). Recently, Oh and colleagues showed that b-cell-derived EVs can directly trigger the differentiation of bone marrow mononucleated cells into insulin-producing cells (149). These findings suggest that stem cell-derived EVs may serve as possible mediators for the development of insulin-producing cells from non-beta pancreatic cells.…”
Section: Effects Of Stem Cell-derived Evs On Endogenous B-cell Prolif...mentioning
confidence: 99%